Korelasi Emotional Eating, Penggunaan Media Sosial, dan Konsumsi Junk Food dengan Kegemukan pada Mahasiswa: Correlation of Emotional Eating, Social Media Use, and Junk Food Consumption with Overweight and Obesity in College Students - Arib, Muhammad Althof Salman; Rosdiana, Delita Septia; Astuti, Widya; Sentani, Muchamad Rizki; Arib, Muhammad Althof Salman Arib (Jurnal Ilmu Gizi dan Dietetik, 2025)
Overweight and obesity have emerged as global health issues, including in young adults such as university students. These conditions are caused by the excessive build-up of adipose tissue, leading to body weight above the normal range. A BMI over 25 kg/m² indicates this state. Factors influencing overweight and obesity among university students include emotional eating habits, time spent on social media, and junk food intake frequency. This study aims to examine risk factors associated with overweight and obesity among students at Universitas Pendidikan Indonesia (UPI). A cross-sectional method with proportional sampling across nine faculties was applied. The sample consisted of 46 UPI undergraduate students, selected using the Lemeshow formula with a 10% error margin. Chi-Square was used for bivariate analysis. The findings revealed a significant relationship between emotional eating (p=0.037) and overweight and obesity. Meanwhile, no significant association was observed for social media duration (p=0.861) or junk food consumption frequency (p=0.732) with overweight and obesity.